QUALITY CONTROL IN PRIMARY HEALTHCARE IN SAUDI ARABIA: A SYSTEMATIC REVIEW - 1-Yusuf ahmed ail al ishaq- 2- Saleh Fares Muhammad Al-Qarad- 3-Hadi mohammedHadiAlsharyah 4-Ahmed Salem Marai Al german 5-RAED MOHAMMED ABDULLAH ALYAMI 6-Ali mana nasserAlhutaylah 7-Hussain mana nasserAlhutaylah -8-ABDULRHMAN AHMAD KHALID MOHAMMAD (Chelonian Research Foundation, 2023)
The quality of primary healthcare is crucial for ensuring efficient and effective patient care, particularly in rapidly evolving healthcare systems like that of Saudi Arabia. With ongoing reforms aimed at improving healthcare delivery, there is a pressing need to assess the state of quality control within primary healthcare settings. This systematic review aimed to evaluate the effectiveness of various quality control interventions implemented in primary healthcare centers in Saudi Arabia, focusing on their impact on patient care and system efficiency.